تأثير الأخطاء في تصميم و تطبيق التعويضات الثابتة على الصفيحة القشرية الدهليزية للدعامة - يوسف, تهامة (Latakia University Journal -Medical Sciences Series, 2018)
تشكل الأخطاء في التعويضات الثابتة خطر كبيرا على صحة النسج حول السنية . تهدف هذه الدراسة الى الكشف المبكر للاصابات حول السنية الناجمة عن الأخطاء في تصميم وتطبيق التعويضات الثابتة. تتألف عينة البحث من 15 دعامة موزعة على 15 مريض تتراوح أعمارهم بين (18– 50) سنة، لديهم تعويضات ثابتة يتراوح عمر التعويض (1-3) سنوات المتوسط الحسابي لها 2 سنة. أظهرت نتائج هذه الدراسة الدور السلبي للتعويضات الثابتة السيئة على امتصاص الصفيحة الدهليزية القشرية من خلال الحواف الطويلة للتعويضات الثابتة /تسرب الاسمنت المثبت / تشكل الكتف المعكوس المثبت للويحة/ تغير طبيعة اللويحة الجرثومية. The failiers in fixed prosthodontics are very dangerous on the health of the periodontics. This study aims to early diagnose the periodontitis caused by the failiers in the designe and application of fixed prosthodontics. The study sample consists of 15 abutments in 15 patients aged (15-50) years with fixed prosthodontics aged (1-3) years. (Average 2 years) The results show the negative effect of bad prosthodontics on the absorbtion of the buccal cortical plate due to very long margines of the prosthodontics, the leakage of the adhesing cement and the beveldsholdermargines that play a role in changing the periodontal biofilm.